2018
DOI: 10.1534/g3.118.200314
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence and Comparative Genomics Analysis of Multi-drug Resistant Environmental Staphylococcus epidermidis ST59

Abstract: Staphylococcus epidermidis is a major opportunistic pathogen primarily recovered from device-associated healthcare associated infections (DA-HAIs). Although S. epidermidis and other coagulase-negative staphylococci (CoNS) are less virulent than Staphylococcus aureus, these bacteria are an important reservoir of antimicrobial resistance genes and resistance-associated mobile genetic elements that can be transferred between staphylococcal species. We report a whole genome sequence of a multidrug resistant S. epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
5
21
0
Order By: Relevance
“…The presence of the sesJ gene in an MGE raises the possibility of its transfer to S. aureus. Another CWA protein, called Pls, has been reported in the J region of SCCmec type 1 and ⌿SCCpls in S. aureus and in an SCC element in S. epidermidis (25,42,43). In our study, we observed the presence of the sesJ gene in ACME IV and ACME V. Previous work by O'Connor et al on the prevalence of ACME in S. epidermidis also reported the presence of different CWA proteins in MGEs.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of the sesJ gene in an MGE raises the possibility of its transfer to S. aureus. Another CWA protein, called Pls, has been reported in the J region of SCCmec type 1 and ⌿SCCpls in S. aureus and in an SCC element in S. epidermidis (25,42,43). In our study, we observed the presence of the sesJ gene in ACME IV and ACME V. Previous work by O'Connor et al on the prevalence of ACME in S. epidermidis also reported the presence of different CWA proteins in MGEs.…”
Section: Discussionsupporting
confidence: 76%
“…In recent years, more genomes of S. epidermidis from other sources were reported and analyzed. Apart from those isolated in clinical settings, analysis of a strain G6_2 isolated from the general public environment in London representing ST59 was described ( Xu et al, 2018 ). Comparative genomic analysis of this strain focused more on the antibiotic resistance and its virulence gene arsenal.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings regarding virulence genetic determinants are concordant with those found in SE isolates from hospitals and commensal strains isolated worldwide. The most prominent features of these isolates are their ability to form biofilms, the presence of PMSs, and the multidrug resistance profile displayed (Otto, 2014; Xu et al, 2018). Employing a phylogenetic strategy using the ccrA, B, C recombinases, we conclude that most of the INPer SE strains carry the SCC mec type IV.…”
Section: Discussionmentioning
confidence: 99%